The Implementation of Gamification System in Asian Higher Education Teaching - Desman Hidayat (Bina Nusantara University, 2017)
Low level of in-class participation can be a problem for lecturers when they teach Asian students. One of the reason is the characteristics of the Asian students, which are quiet and passive. Active learning is needed to solve this problem. Gamification is one of the things that can improve active learning. This study aims to understand how to design gamification system for higher education teaching, the factors contributed to the gamification system in higher education, and the impacts of the gamification system for students with the case study of Bina Nusantara University in Indonesia. The finding shows that there are several things to consider in designing gamification system. Factors in the system, the lecturers, the course, and the students also take important parts in the implementation. When it is done correctly, there will be a lot of positive impacts for the students and the teaching.